Efeito dos Diferentes Níveis de Inclusão de Óleo de Coco e Cafeína nos Desempenhos Zootécnico e Reprodutivo do Astyanax Altiparanae - Bitencourt, Gisele de Freitas (2019)
An experiment was conducted at the Federal Institute of Education, Science and Technology of Espírito Santo - Campus Alegre. The experimental design was completely randomized, constituting a 4 x 3 factorial scheme composed of four levels of coconut oil (FA1 = 0%, FA2 = 2%, FA3 = 4% and FA4 = 6%) and three caffeine (FB1 = 0,00, FB2 = 0,16 and FB3 = 0,32 g of caffeine.kg-1 of feed) with four replicates, totaling 48 experimental units in each experiment. The experimental diet used was isoprotein (32% crude protein) and isoenergetic (2900 kcal.kg-1 ). The development of 1.680 Astyanax altiparanae larvae distributed in a density of 5 post larvae / L was evaluated, totaling 35 animals per experimental unit in a static system with continuous aeration. The feeding frequency was four times a day, offered until the satiety of the animals, lasting 21 days. The variables analyzed were: total length, height, weight gain, specific growth rate, total feed intake, individual feed intake, apparent feed conversion and protein efficiency rate.